(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Hepatitis C virus (HCV) is an important human pathogen affecting 120-170 million individuals in the world. Identification of the causative virus genotype is of a significance to both clinical practices and predict the likelihood to therapy response. Objective: To determine the distribution of HCV genotypes/subtypes and its association with response to therapy among newly diagnosed HCV patients. Methods: Fifty patients with confirmed anti-HCV antibodies were included in this study for HCV genotyping in association with response to therapy. Blood samples from patients were subjected to RNA extraction and reverse transcription step; viral load of HCV was measured by polymerase chain reaction (PCR) at time zero, 3 months and 6 months of dual therapy. Response to therapy was measured as a decrease in viral load (2 log or more) and was described as: good (median log is zero after 6 months of therapy), moderate (median log declines more than 2 log but not zero after 6 months of therapy), poor (median log does not decline or decline less than 2 log after 6 months of therapy). Results: Two genotypes of HCV were detected, genotype 4 was the predominant (27/50, 54%) followed by genotype 1 (23/50, 46%). For HCV subtypes, subtype 1a was of highest percentage (28%) followed by 4e (24%), 1b (18%), 4a (14%), 4b (12%), and 4e (4%).The results revealed a significant association between HCV subtypes, but not genotypes, with response to therapy. HCV subtype 1a followed by 4a showed the highest rate of response 85.7% and 71.4%, respectively, while interestingly HCV subtype 4d showed no response and 1b showed poor response 11.11%. Conclusion: HCV subtypes of great importance in predicting success to HCV therapy and it is believed this would affect the newly emerging directly acting drugs as well. Keywords: HCV, genotypes, response to therapy Citation: Abdulhassan LJ, Abdulamir AS, Alkhalidi NM, Alwaysi SA. Frequency of hepatitis C virus genotypes /subtypes association with response to therapy in a sample of HCV infected Iraqi patients. Iraq. Iraqi JMS. 2018; Vol. 16(1): 30-40. doi: 10.22578/IJMS.16.1.6